Determinación productiva del uso de cinco tecnologías aplicadas en palma aceitera (Elaeis guineensis Jacq.) en el sitio Las Golondrinas, cantón Quinindé, provincia de Esmeraldas. - Mendieta Vivas, Renato (2010)
The present work was realized in Olepsa plantation, ubicated in Esmeraldas province, District of Rosa Zarate. This plantation is localized at 150 m above sea level and at 0° 26' latitud Sourt and 79° 24'longitud West. The study place has an anual 3410 mm of rain fall, an average temperature of 25°C and 749 hours of sun bright. In the investigation the major objectif was to determinate the producing rentabiliti of 5 production ways of tree palm plantation. Moreover, secondary goals were to evaluate the relation between harvest cicles, fertilization cicles, and pruning on average bunches weigh. The experiment was performed under a design in a randomized complete block with five treatments and four replications that resulted from the use of five technologies to manage oil palm six years of age. The treatments tested were: TI Control (Management in Olepsa), T2 (regular pruning crop every 14 days + crown + manual), T3 (regular pruning crops every 7 days + crown + manual), T4 (+ regular pruning crops every 7 days Optimum fertilization + crown + manual) and T5 (regular pruning crops every 7 days + crown optimal chemical fertilizer). In functional analysis and comparisons were made orthogonal to the mean test was used least significant difference (LSD) at 5%. The research measured the variables: increased female inflorescences, number of stems and fresh fruit weight, yield t I ha, and production costs. The results in the increase of female inflorescences were: T1 (55%), T2 (21 %), T3 (13%), T4 (48%), T5 (41%). The number of clusters: the Ti (1020), T2 (1086), T3 (1253), T4 (1080) T5 (1300), production (tons) of fresh fruit: T1 (10.17), T2 (10.73), T3 (12.37) T4 (11,10)1 T5 (13,10)1 and net profit ($): erl (668.11), T2 (739.91) T3 (998.71), T4 (762.68) and T5 (1142.52). As a conclusion, investigation shows us that realize 2 pruning per year, have 7 days harvest cicles, realize an optimal fertilization, but also have a quimical weed managment improve production and rentability of a six years old palm tree farm.